Raw hourly weather records from Fedearroz’s station in Saldaña, Tolima, Colombia - Federación Nacional de Arroceros, Colombia (2016)
Raw hourly weather records from Fedearroz’s station located in Saldaña, Tolima, Colombia. Five variables available: Precipitation (RAIN), minimum temperature (TMIN), maximum temperature (TMAX), relative humidity (RHUM), and solar energy (ESOL). See variables units in README.txt